2006
DOI: 10.1515/znc-2006-7-816
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Auxins on the Biosynthesis of Isoprene Derivatives in Callus Cultures of Vaccinium corymbosum var. bluecrop

Abstract: Callus cultures of Vaccinium corymbosum var. bluecrop were optimized for their isoprene derivatives production by supplementing Schenk-Hildebrandt (SH) medium with constant concentration of kinetin (2.32 μm) and two different amounts of selected auxins. Every auxin, except for IBA, used in 10-time higher concentration (2,4D, NAA, IAA, NOA) stimulated biosynthesis of -sitosterol and inhibited triterpene synthesis. Quantitative analysis of isoprene derivatives in callus biomass collected on the 25 th day of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Beta-sitosterol has been isolated from the cultured tissues of Terminalia chebula [31] as well as the callus of several plants viz. Morus alba [32], Vaccinium corymbosum [33], Cissus quadrangularis [34]. Bathoju and Giri [35] (2012) also reported the production of two important sapogenins; stimasterol and hecogenin from the in vitro regenerated root cultures of C. borivilianum.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-sitosterol has been isolated from the cultured tissues of Terminalia chebula [31] as well as the callus of several plants viz. Morus alba [32], Vaccinium corymbosum [33], Cissus quadrangularis [34]. Bathoju and Giri [35] (2012) also reported the production of two important sapogenins; stimasterol and hecogenin from the in vitro regenerated root cultures of C. borivilianum.…”
Section: Discussionmentioning
confidence: 99%
“…Given this diversity of effects, it is difficult to standardize responses related to the effects of auxins on different species, including their influences on secondary metabolism. However, some auxins can stimulate triterpene biosynthesis (Migas et al 2006;Singh et al 2015;Rasool and Mohamed 2016). Smolenskaya et al (2007) found that 2,4-D induced mitosis in Panax ginseng cells, which resulted in a very low accumulation of ginsenosides (steroid glycosides and triterpene saponins), whereas the NAA induced low cell mitosis and promoted cellular elongation, nuclear DNA synthesis, and the biosynthesis of the same and different ginsenosides.…”
Section: Influence Of Auxinsmentioning
confidence: 99%
“…A modified callus growing medium, supplemented with growth regulators of the auxin group, resulted in the production of a triterpene-rich callus culture and β-sitosterol accumulation. β-sitosterol accumulated in amounts which were approximately 10-times higher than for triterpene acids (oleanolic and ursolic acid) and approximately 6-times higher than for amyrines (α-and β-amyrin) (Migas et al, 2006). Auxin and cytokinin have not been elsewhere reported to have functions in inducing triterpene production.…”
Section: D211 Developmental Regulationmentioning
confidence: 78%
“…On the contrary, the exogenous application of cytokinins in C. roseus cells in a 2,4-D-free medium greatly enhanced the accumulation of the indole alkaloid ajmalicine (Yahia et al, 1998). The influence of auxins on isoprene derivatives was investigated in callus cultures of Vaccinium corymbosum var bluecorp (Migas et al, 2006).…”
Section: D211 Developmental Regulationmentioning
confidence: 99%
See 1 more Smart Citation